Effect of Different Methods of Icing on the Quality of Squid and Cuttlefish During Storage - V., Prafulla; Francis, Liju; P.T., Lakshmanan (Fishery Technology, 2025)
Quality changes in squid (Loligo duvauceli) and cuttlefish (Sepia pharaonis), stored under various conditions, viz; (i) direct icing (ii) indirect icing, and (iii) in a mixture of ice and salt at 3% level were evaluated by chemical and sensory methods. The rate of nucleotide degradation was slow for samples kept in the mixture of ice and salt. K-values of samples kept out of direct contact with ice increased at a faster rate than the other two. However, K-values and nucleotide related products showed significant correlation with sensory scores, under these conditions. Total volatile base nitrogen and trimethyl amine nitrogen exhibited a steady and faster rise for indirectly iced samples. There was a significant loss of soluble nitrogenous components and salt in directly iced samples while there was very little loss (